Ingesta alimentaria y su relación con el estado nutricional en estudiantes de 6 a 12 años en la Escuela Fiscal Mixta “14 de junio”, Vinces, Los Ríos, mayo – septiembre 2019 - Bustamante Triana, Cristhian Omar (2019)
He development of the research carried out at the Mixed Fiscal School June 14 of the city of Vinces, shows that one of the weaknesses presented by children aged 6 to 12 years is the lack of good nutritional practices that allow them to develop a state adequate nutritional, because today the type of food is the necessary means for the determination of healthy eating habits in children at a stage close to adolescence, which is conditioned by various factors, denoting that they do not have nutrition adequate, which is why the general objective is to identify the relationship between food intake and nutritional status in students. The methodology is made up of a quantitative approach because information obtained through indicators was processed, and the correlational, explanatory and anthropometric method was also used, accompanied by a type of field, exploratory and cross-sectional research, together with the techniques and instruments that allowed data collection. The results show 62% with a normal imc, 23% overweight and 15% obesity, in the frequency of consumption showed that schoolchildren who consume frequent and very frequent cereals, fats, processed foods are overweight and obese, while the population that consumes very frequent and frequent fruits, vegetables, have a normal nutritional status. It is concluded that when the variables were related, the statistically significant relationship was demonstrated.